What Is the Role of AI in PTSD Treatment? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Post-Traumatic Stress Disorder (PTSD) is a significant global health challenge, affecting a substantial portion of the population who have experienced trauma...
Keywords: AI in Mental Health; Treatment; Artificial Intelligence; Machine Learning; Healthcare; Digital Health